THE RELATIONSHIP OF DIET WITH INCREASED CHOLESTEROL LEVELS OF ELDERLY IN DILABAN VILLAGE, MENGANTI SUB-DISTRICT, GRESIK REGENCY - Fiddaroini, Fakhrun Nisa’; Ana, Karisma Dwi; Sholikhah, Dwi Uswatun (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2024)
Background: One of the factors causing the increase in cholesterol levels in the elderly is an unhealthy diet, namely consuming high-fat foods such as offal, meat, and coconut milk of food. An unhealthy diet for the elderly, namely consuming high-fat foods such as offal, meat, and coconut milk foods can result in increased cholesterol. Objectives: The study aimed to determine the relationship between diet and increased cholesterol levels of the elderly in Dilaban Village, Menganti Sub-district, Gresik Regency. Methods: The design of this study is a correlational analysis with a cross-sectional approach. The population in this study was all elderly people who suffer from cholesterol at the Posyandu for the Elderly in Dilaban Village, Menganti Sub-district, Gresik Regency in May-August 2023, a total of 63 people. The sample size of this study was 54 respondents. A side technique of this research is using a simple random sampling. Data analysis technique using chi-square test. The instrument used was the Food Frequency Questionnaires (FFQ) questionnaire to measure eating patterns, while the increase in cholesterol levels was measured by observation. Results: The result of this study showed that most respondents' eating patterns were poor as many as 41 respondents (75.9%), most respondents had high cholesterol levels as many as 35 respondents (64.8%). The result of the chi-square test showed that p-value = 0.000 < α = 0.050 so that H1 was accepted, so there was a relationship between diet and increasing cholesterol levels in the elderly in Dilaban Village, Menganti Sub-district, Gresik Regency. Conclusion: Efforts made by health workers so that the elderly does not experience an increase in cholesterol levels are providing communication, information, and education to the elderly so that they maintain their diet and their cholesterol levels are normal.